Analysis of the Effect of Providing Local Food Supplements on Weight Gain in Pregnant Women with Chronic Energy Deficiency at the Lamparinga and Tetewatu Community Health Centers in North Konawe Regency - Makmur, Heny; Tasnim, Tasnim; Risky, Sartini (Magister Kesehatan Universitas Mandala Waluya, 2025)
Introduction: Chronic Energy Deficiency is a health problem for pregnant women that can lead to premature birth, birth defects, low birth weight, and even death. The prevalence of chronic energy deficiency in 2022 at the Lamparinga Community Health Center was 11.8% and at the Tetewatu Community Health Center 8.3%. The purpose of this study was to analyze the effect of providing local food supplements on weight gain for pregnant women with chronic energy deficiency at the Lamparinga and Tetewatu Community Health Centers in North Konawe Regency. Method: The type of research is quantitative (Quasi-experiment), with a pre-test, post-test, control group design. The population was 64 pregnant women with chronic energy deficiency in the working area of the Lamparinga and Tetewatu Health Centers in January 2024, and a sample of 18 people using cluster random sampling. Data were analyzed using the independent t-test, Mann-Whitney U test, and Kruskal-Wallis test. Result: The results of the study obtained an average control weight of 48.67 kg pre-test and 48.66 kg post-test, intervention weight, 50.2 kg pre-test and 51.9 kg post-test. The results of the independent t-test p-value 0.001 and the results of the Kruskal-Wallis analysis obtained a p-value of 0.001 on the body weight variable. Conclusion: Providing local food supplements on increasing the weight of pregnant women with chronic energy deficiency and the effectiveness of providing local food supplements on increasing the weight of pregnant women with chronic energy deficiency at the Lamparinga and Tetewatu Health Centers.